A palavra na vida e na escola: um estudo sobre fatores fundamentais na constituição da escrita autoral - Tovar Nelson Pereira Júnior (2015)
The present research sought to understand the factors that influence significantly the construction of authorial writing. In order to do so, the opinion piece genre was studied via pieces written by six students of the second year of high school from a federal institution in Minas Gerais, as well as their sociocultural profile and formal route of education as readers and writers in which they have been and still are inserted. The conceptual complex of Bakhtins philosophy of language (2003, 2010, 2013) is used as general theoretical background with the concept of cultural capital by Pierre Bourdieu (2007) for data analysis. These led the research towards the establishment of a relationship between cultural and written formation. The study was conducted within a qualitative-interpretive perspective both in the analysis of observable authorship levels in the studied written production and the treatment of data constituted by the surveys and interviews composing the dissertations corpora. Within the limit established by the researchers studying the authors manifestation in the opinion piece genre produced by high school students the results allowed the explicitation of three factors as fundamental for the construction of authorial writing: parents length of formal education (understood as cultural capital, valued in the scholar market); mothers influence and other relatives within a subjects social circle; and the schools role. For this study, carried out in the field of Applied Linguistics and Teaching of Portuguese, it is important that the theoretical results be read as a possibility of support for a practical intervention that may transform the still challenging panorama of Brazilian education, within which we find the processes of teaching and learning and text production.